2013
DOI: 10.4028/www.scientific.net/amr.789.476
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of CO<sub>2</sub> Corrosion of API 5L X52 Steel in NaCl Solution under Turbulent Flow Condition

Abstract: The presence of carbon dioxide (CO2) and water in the fluid can cause severe internal corrosion in the pipelines. This study aims to observe corrosion behavior during the changes in flow rate and acidity conditions in order to obtain the relationship between the parameters by the measured corrosion rate. Corrosion rate measurements were performed for API 5L X52 steel material by using polarization method in 3.5% NaCl solution with saturated CO2 injection. Solution with different acidity were applied which has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The working electrode was inserted and operated at a speed of 1000 rpm through connection to a Pine Model MSRX electrode rotator. The rotating electrode with speed of 1000 rpm was prepared for simulating turbulent flow conditions related to data obtained in real life system [24][25][26][27]. The electrochemical cell was connected for LP measurement.…”
Section: Linear Polarization (Lp)mentioning
confidence: 99%
“…The working electrode was inserted and operated at a speed of 1000 rpm through connection to a Pine Model MSRX electrode rotator. The rotating electrode with speed of 1000 rpm was prepared for simulating turbulent flow conditions related to data obtained in real life system [24][25][26][27]. The electrochemical cell was connected for LP measurement.…”
Section: Linear Polarization (Lp)mentioning
confidence: 99%
“…Most studies have dealt with different corrosion environments, such as freshwater, seawater, and NaCl for API 5L series. For pH value under turbulent flow conditions, the results showed that the corrosion mechanism was mainly controlled by mass transport at pH=4 (Rustandi et al 2013). In addition, different pH values and concentrations of various exposed solutions affect the corrosion behavior of heat-treated samples (Sharma and Chhibber 2019).…”
Section: Introductionmentioning
confidence: 96%